Economics of a Gasification Based Mini Grid - a case study of a 10 kW Unit in Uganda - Da Silva, I. P.; Buchholz, T.; Volk, T; Tennigkeit, T; Da Silva, Izael (My University, 2007)
Small-scale wood gasification systems have the potential to contribute to the rural electrification in Uganda. This paper presents an economic analysis of a 10 kW gasifier unit and its minigrid installed on a Ugandan farm. The bioenergy system has been running stable on a six hour daily base for seven months. When the gasifier is operated close to the rated capacity, the gasifier system is economically attractive compared to diesel generated electricity Results indicate that replicating successful wood gasification systems stipulates integration of sustainable fuelwood supply and viable business models.
Conference Proceedings of the Industrial and Commercial Use of Energy